Legal Certainty or Symbolic Gesture? A Political Reappraisal of Indonesia Health Practitioner - Laksono, Stepanus Agung; Fakih, M; Putri, Ria Wierma (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The cessation of healthcare services has traditionally required informed consent from the patient or their legal representative. However, with the enactment of Article 273 paragraph (2) of Law No. 17 of 2023 on Health, Indonesian medical personnel are now permitted to halt services unilaterally when faced with acts of violence, harassment, or degrading treatment. While this provision affirms the importance of healthcare worker safety, it also creates legal and ethical dilemmas, particularly regarding the limits of professional duty and the risk of being accused of negligence. The legal ambiguity surrounding the implementation of Article 273 further complicates the responsibilities of healthcare providers and the protection mechanisms available to them. In response to these challenges, this study addresses three main objectives: (1) to examine the scope of legal protection afforded to medical personnel who terminate healthcare services under Article 273, (2) to analyze the ethical and legal responsibilities that arise from such actions, and (3) to assess the political and institutional context that shaped the article’s development, as well as the practical barriers to its enforcement. By combining doctrinal legal analysis with a legal-political perspective, this research contributes to a more comprehensive understanding of how law, policy, and ethics intersect in regulating healthcare delivery in conflict-prone settings.